Peningkatan umur simpan cabai merah dengan edible coating kitosan cangkang kerang hijau dan ekstrak sereh - Nia Kartika Putri; Mahfirotuz Zahra; Wifia Febriana; Navida Nur Kholifah; Carissa Salsabila; Yunan Kholifatuddin Sya’di (AGROINTEK, 2026)
Red chili is a highly perishable commodity with a short shelf life, making it prone to damage and spoilage. One effective method to extend its shelf life is by applying an edible coating made from chitosan derived from green mussel shells and lemongrass extract, both known for their antibacterial properties and ability to form a protective layer. This study aimed to assess the effectiveness of this edible coating in prolonging the shelf life of red chilies. The parameters measured included weight loss, vitamin C content, water content, total microbial count, and sensory evaluation through a hedonic quality test for texture and color based on panelist assessments. A Completely Randomized Factorial Design (CRFD) was employed, with two factors: variations in chitosan concentration and storage duration at low temperatures. Observations were made over four weeks, with weekly measurements starting from the second week. The results showed that the edible coating significantly reduced weight loss, helped maintain vitamin C content, stabilized water levels, preserved texture and color, and controlled microbial growth compared to untreated chilies. The optimal results were observed with 3% chitosan stored for four weeks, showing the lowest weight loss (2.81%), the highest vitamin C retention (181.9 mg), and minimal microbial growth (1.4 x 10⁴ CFU/g). These findings demonstrate that chitosan-based edible coatings effectively enhance the shelf life and quality of red chilies.